DFT Insights into the Physical Properties of Layered LiMnSe2 and LiMnTe2 Compounds - Benmakhlouf, Abdennour; Faid, Fares; Ghermoul, Nedjmeddine; Ozdogan, Kemal; Helaimia, Taoufik; Bouhemadou, Abdelmadjid; Galanakis, Iosif (MDPI, 2024)
Using state-of-the-art first-principles electronic-band-structure calculations alongside density functional theory, we investigated the structural, elastic, electronic, and magnetic properties of LiMnZ(2) (Z = Se, Te) compounds with a trigonal structure. Initially, we determined the equilibrium lattice structure and atomic positions, which aligned well with experimental values. Ferromagnetism was shown to be more favorable than the non-magnetic state. The elastic constants, cohesive energies, and formation energies indicated that the studied compounds were mechanically stable in the experimentally determined trigonal lattice. The analysis of spin-polarized band structures and density of states revealed that both LiMnZ(2) compounds exhibited perfect half-metallic characters. The total spin magnetic moment per formula unit adhered to the Slater-Pauling rule, being exactly 4 mu(Beta), mainly concentrated at the Mn atoms due to the strong spin polarization of the Mn d orbitals. We anticipate that our results will prompt further experimental and computational studies for the application of these layered materials in practical devices.
Keywords: first-principles calculations; electronic band structure; ferromagnetism; half-metal; elastic properties; Slater-Pauling; layered transition-metal dichalcogenides; SPIN-POLARIZATION; CS; AMNTE(2); RB; LI; Materials Science; Metallurgy & Metallurgical Engineering